Cerebellar tomographic attenuation of healthy felines - Babicsak, Viviam Rocco [UNESP]; Silva, Luciana Carandina da [UNESP]; Cardoso, Guilherme Schiess [UNESP]; Vulcano, Luiz Carlos [UNESP]; Machado, Vania Maria de Vasconcelos [UNESP] (Univ Federal Rural Pernambuco, 2011)
The cerebellum is responsible for coordination and maintenance of the fine control of muscle contraction. In cases of a suspected cerebellar disorder, a computed tomography scan can be performed to identify structural change. The aim of this study is to describe the cerebellar tomographic attenuation values in healthy cats since this variable is considered of great importance in the evaluation of images obtained by this imaging modality. A simple and a contrast enhanced brain computed tomographic scan were performed in 15 adult cats with no history of neurological symptoms and negative for feline leukemia and immunodeficiency virus. After acquiring the image, the measurement of the average attenuation of a cerebellar area of 2 centimeters in diameter was obtained. The cerebellar tomographic attenuation showed a variation from 14.60 to 25.50 HU in the simple scan and from 25.50 to 33.40 HU in the enhanced phase. Most animals (73.33%) had precontrast cerebellar attenuation values within the stipulated limit for the brain in a previous study (20-41 HU). Four animals in this study (26.67%) had values lower than 20 HU, which can be explained by differences in cellular composition between these two regions. The average value of contrast enhancement was 4.91 HU, and in none of the animals an enhancement greater than 10 HU was observed, which is in agreement with previous studies.
Keywords: computed tomography; cerebellum; felines